Forward Guidance Contracts - Yulin Liu; Hans Gersbach; Volker Hahn (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We examine "Forward Guidance Contracts", which make central bankers' utility contingent on the precision of interest-rate forecasts. We integrate those contracts into the New Keynesian Framework and study how they can be used to overcome a liquidity trap. We establish the properties of simple renewable Forward Guidance Contracts and characterize the contracts that the government wants to offer repeatedly. These contracts create favorable tradeoffs between the efficacy of forward guidance at the zero bound and the reduced flexibility in reacting to future events, and dominate long-term contracts for moderate negative natural real interest-rate shocks. We discuss which type of Forward Guidance Contracts can be used when there is uncertainty about natural real interest-rate shocks, a situation which typically calls for moderate incentive intensity. Finally we explore alternative contractual environments.
Keywords: E52; E58; E31; 330